Synonymy in Neotropical Ceratopogonidae (Diptera: Culicomorpha) - Spinelli, Gustavo Ricardo (2019)
Based on the study of type specimens, Forcipomyia galliarii is recognized as junior synonym of Forcipomyia platensis, and Alluaudomyia biestroi of Alluaudomyia catarinensis. New records of both species from Argentina are given.